Prevalensi Jenis Kelamin dan Penyebab Kematian Bayi pada Kasus Infanticide di RSUD Dr. Moewardi Januari 2006 â Desember 2011 - Setyarini, Rafika Iezza (Nexus Kedokteran Komunitas, 2012)
Background: Nowadays, babies murder right after born or we can call it infanticide, spontanously or well-planned, has increased. The purpose of this study was to find out the prevalence of sex-related infanticide and the causes on RSUD Dr. Moewardi. Methods: This was an observational retrospective study. Sample of this study was the victim of infanticide and was chosen by purposive sampling with total sample were 24 cases. Then all variables were analyzed using Chi Square Test. Results: This study found 24 cases of infanticide, 4 cases on 2006, 5 cases on 2007, 6 cases on 2008, 5 cases on 2009, 1 case on 2010, and 3 cases on 2011. There are 17 cases of male infanticide and 7 cases of female infanticide. The causes of babiesâ death were asphyxia (13 cases), Caffy Syndrome (7 cases), blunt trauma (4 cases). Chi Square Testâs result is statistically not significant (p: 0.104). Conclusions: The prevalence of male infanticide is higher than female infanticide. The most cause of babiesâ death is asphyxia and there is no corelation between the sex and the death causes. Keywords: infanticide, sex-related, cause of deathÂ